OPTIMIZATION OF INJECTION MOLDING PROCESS PARAMETER SETTINGS USING 3k GENERAL FACTORIAL DESIGN AND DATA VISUALIZATION - Wilson Kosasih; Lithrone Laricha Salomon; Suhartono; Maria A. Kartawidjaja; Melisa Mulyadi (Jurnal Ilmiah Teknik Industri, 2023)
This paper discusses an experimental design approach to optimize injection molding process parameter settings according to quality targets. The method used is general factorial design, so that it can investigate the effect of each predictor variable (factor) and its interaction effect. In this study, front barrel temperature, injection pressure, holding pressure, and holding time were selected as control factors. Before testing the hypothesis, the results of the experiment are also illustrated to summarize what main characteristics phenomena the data visualization can convey us. Hypothesis testing used linear regression analysis and analysis of variance (ANOVA) with a significance level (a) of 0.05. The results demonstrated that front barrel temperature (A), injection pressure (B), holding pressure (C), and holding time (D) had a significant effect on tensile strength, but only the front barrel temperature factor had a significant effect on net weight. Front barrel temperature is the most influencing factor on the response variables. There are a significant effect of the interaction between factors, namely AB, AC, BC, ABC, ABD, BCD, on tensile strength, whereas only AB interaction has a significant effect on net weight. The optimal settings could be adjusted according to the required quality target.